Adaptation and Mitigation of Climate Change In The Qur’an Based on Salman’s Interpretation - Sabila, Alya; Maharani, Fitri; Nur Amalia, Intan; Fadilah Fauziah, Nurul; Ceriani, Gladis; Naelin Najihah, Bannan (Journal of Ulumul Qur'an and Tafsir Studies, 2024)
This research focuses on Salman's interpretation of QS Quraish and Ar-Rum: 41, which links the seasonal travel habits of the Quraish to this verse. Using a historical approach and environmental analysis, this research investigates how climate change and seasonal travel influenced trade travel and the spread of religion, particularly in the context of the Silk Road. Tafsir Salman highlights that the seasonal travel habits of the Quraish are reflected in the verses of QS Quraish and Ar-Rum: 41, which invite them to worship God who provides sustenance and protection during the journey. This research also links seasonal travel habits to climate changes that affected the Quraish trade routes, as well as their impact on the spread of religion. In addition, this research highlights the negative impact of human activities, such as increasing CO2 emissions, on environmental balance, which is also discussed in Salman's interpretation. Thus, this research provides an in-depth understanding of the complex relationship between historical, environmental and religious factors, as well as the importance of maintaining environmental balance in the context of the religious values ​​taught by Islam, as interpreted in Salman's interpretation.